2013
DOI: 10.1371/journal.pone.0057565
|View full text |Cite
|
Sign up to set email alerts
|

Migratory New World Blackbirds (Icterids) Are More Neophobic than Closely Related Resident Icterids

Abstract: Environments undergo short-term and long-term changes due to natural or human-induced events. Animals differ in their ability to cope with such changes which can be related to their ecology. Changes in the environment often elicit avoidance reactions (neophobia) which protect animals from dangerous situations but can also inhibit exploration and familiarization with novel situations and thus, learning about new resources. Studies investigating the relationship between a species’ ecology and its neophobia have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 43 publications
(53 reference statements)
1
38
0
Order By: Relevance
“…Particularly in birds it has been shown that residents explore more than closely related migrants . Similarly, residents are less neophobic to feed beside a novel object than migrants . Both, high neophilia and low neophobia help residents to find and exploit new resources over the year.…”
Section: Cognitive Adaptations To Stable Environmentsmentioning
confidence: 99%
“…Particularly in birds it has been shown that residents explore more than closely related migrants . Similarly, residents are less neophobic to feed beside a novel object than migrants . Both, high neophilia and low neophobia help residents to find and exploit new resources over the year.…”
Section: Cognitive Adaptations To Stable Environmentsmentioning
confidence: 99%
“…; Echeverría & Vassallo ) and has been supported by investigations into wild birds by Mettke‐Hofmann et al. (). Corvids have been frequently recorded as being wary of unfamiliar items or food types new to the bird's experience (Heinrich ), with Kijne & Kotrschal (, p13) stating that common ravens ( Corvus corax ) often take ‘minutes to months’ before they become familiar with a novel object.…”
Section: Introductionmentioning
confidence: 65%
“…), while fewer have been conducted on wild animals (Mettke‐Hofmann et al. ; Vernelli ). Experiments undertaken by Greenberg (, ) comparing neophobia in swamp ( Melospiza georgiana ) and song sparrows ( Melospiza melodia ) produced contradictory results among wild and captive birds, suggesting that certain experiences in the lives of young wild swamp sparrows increased their neophobia while this was not the case in song sparrows.…”
Section: Introductionmentioning
confidence: 99%
“…However, predation pressure is often spatially and temporally variable (Sih et al 2000;Stankowich & Blumstein 2005), forcing prey to make behavioural decisions in the absence of complete information (ecological uncertainty; Dall et al 2005;McNamara & Dall 2010;Mathot et al 2012). Given that environments may change in an unpredictable fashion due to natural and human-induced factors, the question of how prey adjust to uncertainty in local predation risk has come to the forefront of research on antipredator decision-making (Mettke-Hofmann et al 2013;Mettke-Hofmann 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The dangerous niche hypothesis(Greenberg & Mettke-Hofmann 2001;Mettke-Hofmann et al 2013) posits that prey faced with increased risk (predation risk, competition, unknown foraging opportunities) could reduce the costs associated with 'making a bad decision' by exhibiting increased neophobia. Degrees of freedom = 2, 71 McNamara & Dall 2010).…”
mentioning
confidence: 99%